The Nature of Science Views among Intern General Science Pre-Service Teachers - Somsak Gathong (2020)
© Published under licence by IOP Publishing Ltd. This research aimed to study the nature of science views of 23 students who are currently intern general science pre-service teachers in one of Rajabhat Universities in the North. The research instrument used in the study was: the nature view of science questionnaire developed by Haidar (1999) and the researcher has improved it in accordance with the curriculum of science and education in Thailand. The nature of science views had three aspects totally 27 items. There were 8 items for scientific world view, 4 items for the scientific knowledge inquiry, 6 items for scientific enterprise and they were totally 18 items and open-ended question on the nature of science views with three aspects of science in the world: 3 items for scientific world view, 3 items for scientific inquiry and 3 items for scientific enterprise. They were totally 9 items. Then the data were analyzed by grouping the answers and finding the percentage. The results of the research revealed that intern general science pre-service teachers had the same view of the nature of science that was consistent with 3 aspects of the traditional view. That were the 2nd aspect; scientific inquiry. The 1st aspect; scientific found that 91.30 %better understood consistent with the traditional view that working of a scientist must be based on a scientific method that has a definite sequence of steps. As the 2nd aspect; the scientific knowledge creation found that 78.26% had the consistency of understanding with the traditional concept. It stated that scientific knowledge is created by observation, survey or experiment. The 3rd aspect; evidence and imagination, and creative thinking, it affects the scientific knowledge creation. It showed that 73.91% had an understanding that is consistent with the traditional concept that scientists acquire scientific knowledge using only evidence-based. The findings indicated that intern general science pre-service teachers still have many points of view. The most necessary thing is teachers need to use teaching and learning methods that solve the problem of natural science erroneously in the course of learning science management before the students go for the practicum.